The Student Volunteer Movement for Foreign Missions and Its Contribution to 20th Century Missions - Harder, Ben (Missiology, 1980)
Tracing the history of the Student Volunteer Movement, Professor Harder sheds light on this forerunner of Christian student organization. Its significant impact on the worldwide mission of the church in its day has raised the hope that this type of movement may reoccur out of today's growing student interest in world mission.